Cognitive and Affective Aspects of Verbal Humor: A Visual-World Eye-Tracking Study - Israel, Laura; Konieczny, Lars; Ferstl, Evelyn C. (Frontiers in Communication, 2022)
Many theories of verbal humour postulate that the funniness of jokes is caused by an incongruency in the punchline whose resolution yields a feeling of mirth. While there are studies testing the prediction that this situation model updating leads to increases in processing costs, there are few studies directly assessing the time course of when the alternative situation models are entertained. In a visual world paradigm, stories were presented auditorily and displays were presented illustrating either the situation implied by the context or the final interpretation after the punchline. Eye movement data confirmed the switch from the initial to the final interpretation for jokes as well as for non-funny control stories that also required a situation model revision. In addition to these effects of the cognitive revision requirements, the pupil dilations were sensitive to the affective component of joke comprehension. These results are discussed in light of incongruency theories of verbal humour.